Model Regenerasi Ideologi Muslim Melayu Demi Menjaga Eksistensi Melayu Di Riau - Edison, Edison; Mamla Saidah, Elbina (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2024)
The Riau Provincial Government's policy regarding the Preservation of Malay Culture has not yet included a development system to maintain the existence of Malay Muslims. The Malay community still exists in terms of population but is threatened with extinction in terms of understanding and the identity of Malay Muslims. This research aims to design a model for the regeneration of Malay ideology as an effort to maintain the existence of the Malays in Riau. This study employs a literature review method to formulate a model for the regeneration of Malay ideology. The research successfully designed a one-year initial training model for 40 weeks, with the training objectives developed from the four goals of the Preservation of Malay Culture in Riau as outlined in Regional Regulation No. 9 of 2015, Chapter II, Article 3. The study materials were developed from the scope of the preservation of Malay culture in Riau in Chapter III, Article 7, supplemented by the development of materials from the explanation of Gurindam Dua Belas. The learning methods and success measures of the training program were formulated based on the objectives and content of the study materials. Further research is recommended to develop study materials for lifelong regeneration of Malay ideology.